The Music-Related Quality of Life Measure (MuRQoL): A Scoping Review of Its Validation and Application - Giorgos Dritsakis; Andrea Frosolini; Cynthia Lam (Audiology Research)
Background: The Music-Related Quality of Life (MuRQoL) was launched in 2017 as a valid psychometric measure of Cochlear Implant (CI) users’ music experience and its impact on Quality of Life (QoL). This scoping review aimed to explore the implementation and effectiveness of the instrument since its introduction. Methods: PubMed and Google Scholar databases were searched for publications written in English reporting a translation, validation or application of the MuRQoL. Results: Eleven publications were found, including three validated versions and eight studies that applied the MuRQoL in Italy, Turkey, Spain and the US in research and clinical settings for various purposes. The review showcases the reliability, validity and potential clinical utility of the tool underscoring its growing adoption and integration with other assessment tools. Based on the findings, we make recommendations and provide a roadmap for optimizing the use of MuRQoL globally, including naming and terminology conventions. Anecdotal evidence, such as forthcoming or non-English publications offer further insights into the tool’s future potential. Conclusions: The MuRQoL is currently available in four languages and applicable across diverse cultural contexts, populations and settings. It is a versatile, patient-centered tool providing a deep understanding of CI users’ music experiences. As research and validation efforts continue, the instrument has the potential to set a benchmark for assessing the broader impacts of CIs beyond speech perception, emphasizing the significance of music in enriching the lives of individuals with Hearing Loss (HL).